PENGELOLAAN DAN PENGEMBANGAN WAKAF DI KABUPATEN BONE (TELAAH UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF) - Haslinda Haslinda (Institut Agama Islam Negeri Bone, 2020)
AbstractThe result showed that the application of law No. 4 of 2004 have not been fully implemented, but see the purpose of section 42 stressed and allotment of endowments, have been run but not maximized because the issue of the designation only for practice and social activities that are consumptive. Endowments in Bone regency more used to build places of worship and socially useful. Factors inhibiting the development and management of waqf in Bone regency including lack of socialization for goverment agencies regarding endowments, the week role of the istitution ministry of religion in the part of the prevention or data collection on donated land, lack of understanding and awareness among muslims againts waqf that waqf is not managed properly, and last nadzir were less profesional and the lack of human resources (HR) can empower possessions endowment and empowerment strategies endowments in Bone regency perspective of law number 41 of 2004.